Citric acid crosslinked carboxymethyl cellulose edible films: A case study on preserving freshness in bananas - Nongnual, Teeranan; Butprom, Nattawut; Boonsang, Siridech; Kaewpirom, Supranee (My University, 2024)
The study involves the preparation and characterization of crosslinked-carboxymethyl cellulose (CMC) films using varying amounts of citric acid (CA) within the range 5 %–20 %, w/w, relative to the dry weight of CMC. Through techniques such as Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, carbonyl content analysis, and gel fraction measurements, the successful crosslinking between CMC and CA is confirmed. The investigation includes an analysis of chemical structure, physical and optical characteristics, swelling behavior, water vapor transmission rate, moisture content, and surface morphologies. The water resistance of the cross-linked CMC films exhibited a significant improvement when compared to the non-crosslinked CMC film. The findings indicated that films crosslinked with 10 % CA demonstrated favorable properties for application as edible coatings. These transparent films, ideal for packaging, prove effective in preserving the quality and sensory attributes of fresh bananas, including color retention, minimized weight loss, slowed ripening through inhibiting amyloplast degradation, and enhanced firmness during storage.
Keywords: Active package; Carboxymethyl cellulose; Citric acid; Crosslink; Edible film